2010
DOI: 10.1182/blood-2010-03-274860
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired angiogenesis and altered Notch signaling in mice overexpressing endothelial Egfl7

Abstract: Epidermal growth factor-like domain 7 (Egfl7) is important for regulating tubulogenesis in zebrafish, but its role in mammals remains unresolved. We show here that endothelial overexpression of Egfl7 in transgenic mice leads to partial lethality, hemorrhaging, and altered cardiac morphogenesis. These defects are accompanied by abnormal vascular patterning and remodeling in both the embryonic and postnatal vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 41 publications
7
137
0
Order By: Relevance
“…Previous studies have shown that Egfl7 modulates Notch signaling in vivo in mouse embryos and in vitro in HUVECs, human trophoblast cells and neural stem cells (Nichol et al, 2010;Massimiani et al, 2015;Schmidt et al, 2009). To examine whether Egfl7 modulates Notch signaling in the developing placental labyrinth, we performed real time RT-PCR for Notch target genes in pre-placental tissues (E8.5) or placentas (E9.5, E12.5) from C57BL/6J control and Egfl7 −/− mice.…”
Section: Syna Expression Was Significantly Decreased In Egfl7mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Egfl7 modulates Notch signaling in vivo in mouse embryos and in vitro in HUVECs, human trophoblast cells and neural stem cells (Nichol et al, 2010;Massimiani et al, 2015;Schmidt et al, 2009). To examine whether Egfl7 modulates Notch signaling in the developing placental labyrinth, we performed real time RT-PCR for Notch target genes in pre-placental tissues (E8.5) or placentas (E9.5, E12.5) from C57BL/6J control and Egfl7 −/− mice.…”
Section: Syna Expression Was Significantly Decreased In Egfl7mentioning
confidence: 99%
“…Furthermore, egfl7 morphant zebrafish display severe vascular defects, whereas embryos of egfl7 mutant zebrafish and one Egfl7-specific knockout mouse line do not show obvious phenotypes, owing to activation of compensatory genes (Fish et al, 2008;Kuhnert et al, 2008;Nichol and Stuhlmann, 2012;Rossi et al, 2015;Wang et al, 2008). Conversely, endothelial-specific overexpression of Egfl7 in mice results in vascular defects during embryogenesis and pathological vascularization in the neonatal retina (Nichol et al, 2010;Bambino et al, 2014), suggesting a specific role for Egfl7 in vascular development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFL7 is secreted by endothelial cells and is implicated in the regulation of blood vessel formation and cell migration through interaction with receptors of the Notch family (1,(8)(9)(10)(11). EGFL7 binds to the extracellular domains of all four Notch receptor isoforms and inhibits Jagged-induced Notch signaling (12).…”
Section: Introductionmentioning
confidence: 99%
“…48 EGFL7 has also been demonstrated to antagonize Notch signaling in endothelial cells as well as neural stem cells. 49,50 Again, however, it remains to be determined if RhoA is a direct or indirect downstream target of this pathway.…”
mentioning
confidence: 99%